2020
DOI: 10.26599/bdma.2020.9020024
|View full text |Cite
|
Sign up to set email alerts
|

Multi-attention fusion modeling for sentiment analysis of educational big data

Abstract: As an important branch of natural language processing, sentiment analysis has received increasing attention. In teaching evaluation, sentiment analysis can help educators discover the true feelings of students about the course in a timely manner and adjust the teaching plan accurately and timely to improve the quality of education and teaching. Aiming at the inefficiency and heavy workload of college curriculum evaluation methods, a Multi-Attention Fusion Modeling (Multi-AFM) is proposed, which integrates glob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(30 citation statements)
references
References 21 publications
0
30
0
Order By: Relevance
“…The standard learner starting parameters are learned to adapt to fast gradient changes, and the LSTM metalearner is trained as an optimization method customized to the metalearning job. Authors [ 14 ] investigated a particular example, in which the metalearner must update the classifier using gradient descent, and showed that a reduced model (dubbed MAML) may obtain equal results. Authors [ 15 ] investigated a more complex weight updating approach that yielded slight improvements in few-shot classification performance.…”
Section: Related Workmentioning
confidence: 99%
“…The standard learner starting parameters are learned to adapt to fast gradient changes, and the LSTM metalearner is trained as an optimization method customized to the metalearning job. Authors [ 14 ] investigated a particular example, in which the metalearner must update the classifier using gradient descent, and showed that a reduced model (dubbed MAML) may obtain equal results. Authors [ 15 ] investigated a more complex weight updating approach that yielded slight improvements in few-shot classification performance.…”
Section: Related Workmentioning
confidence: 99%
“…The test results for the Restaurant dataset reached an F1 value of 65.20%, the Laptop dataset only achieved an F1 value of 55.08%, and the Twitter dataset achieved the lowest F1 value (just 47.89%). Zhai et al 23 encountered a similar situation when proposing a model combining many LSTM modules to conduct sentiment analysis for Course, Education, and Restaurant datasets. This model achieved an accuracy of 94.6% on the Education dataset.…”
Section: Introductionmentioning
confidence: 97%
“…The major aim of sentiment analysis [4] is to discover the attitude of bipolar prospects on specific targets in a sentence [41]. In recent years, diverse approaches have been proposed for sentiment analysis by considering the complex text polarity [44]. Several researchers focus on knowing about the sentiments of the texts in various constraints [32].…”
Section: Introductionmentioning
confidence: 99%